PRAGMATISME RASIONAL PENINGKATAN ETOS DAN NILAI MORAL GENERASI STROBERI MELALUI PENDIDIKAN AGAMA ISLAM DI ERA KONTEMPORER - Muhammad Zein Damanik (Jurnal Al Wahyu, 2023)
"Rational Pragmatism: Enhancing Ethos and Moral Values of the Strawberry Generation through Islamic Education in the Contemporary Era" The rational pragmatism, enhancement of ethos, and moral values of the 'Strawberry' generation (a metaphor for the current younger generation) through Islamic Education in the contemporary era creates a robust foundation for character development. The contemporary era brings its own set of challenges where moral values and ethics often seem eroded or overlooked in a rapidly changing society. Islamic Education becomes a strong pillar for building moral and ethical foundations in today's generation. Rational pragmatism is an approach that prioritizes logic, rationality, and fact-based problem-solving. In the context of Islamic education, this approach allows the younger generation to develop a strong understanding of religion not based solely on belief but also through logical and critical thinking. Islamic education in the contemporary era should be able to teach how to apply religious teachings in a rational and practical manner in everyday life. The enhancement of ethos and moral values is a crucial aspect of shaping the character of the 'Strawberry' generation. Islamic education can be a means to strengthen moral values such as honesty, compassion, hard work, simplicity, and responsibility. Through Islamic education focused on the practical application of these values in daily life, the younger generation can gain a deeper understanding of how these values are relevant and beneficial in the contemporary context. Furthermore, in a contemporary era where information is easily accessible, it is important to ensure that Islamic education doesn't remain merely abstract. More than just theory or concepts, Islamic education should provide concrete, relevant understandings of how Islamic principles can be applied in modern situations such as technology, economy, environment, and intercultural relationships. Thus, Islamic education in the contemporary era equips the 'Strawberry' generation not only with religious knowledge but also with critical thinking skills, rationality, and an understanding of the moral values necessary to become useful individuals in an ever-changing society. This leads to the formation of a generation that is not just strong intellectually but also possesses strong character, ethics, and the capability to positively contribute to the dynamics of modern society.